Estrategia didáctica, basada en el aprendizaje colaborativo para potenciar el rendimiento académico de los estudiantes de décimo año de E.G.B en la asignatura de Estudios Sociales - Vallejo Esparza, Valeria Alexandra (2023)
The present work "Didactic strategy, based on collaborative learning to enhance the academic performance of tenth grade students in the subject of Social Studies", was based on the problem of the lack of strategies based on collaborative learning, which has led students not to experience a new methodology of classes, teachers continue to use conservative teaching processes. Therefore, the following objectives were proposed: to know the perception of students on the application of collaborative learning in the classroom and to develop a proposal for a methodological strategy of collaborative learning to enhance academic performance. Its importance lies in renewing their theoretical, scientific and pedagogical conceptions in the construction and use of methodological strategies. A mixed approach methodology was used because it is a social research, a questionnaire and an interview guide were used as instruments to determine the opinion of all those involved by means of questions that facilitate their response. As a conclusion, most students enjoy working in a collaborative environment, allowing them to learn from their peers and contribute their ideas, which enriches the learning process, in addition, working in a team helps students to develop social and emotional skills such as communication, leadership, conflict resolution and empathy.